Determination Model of Community Empowerment Based on Village Typology in Coastal Areas of Gresik - Anita Handayani; Roziana Ainul Hidayati (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The Village Development Index (IPD) is a measure compiled to assess the level of progress or development of the village.  One of the villages that is important for mapping related to village typology is the coastal village. It is widely known that many villages on the coast that have many shortcomings ranging from cleanliness, sanitation, and important for the empowerment of coastal villages. The results of the study were produced that the Category of Developing Villages in Ujung Pangkah Subdistrict is Pangkah Kulon Village, Banyu urip Village, Bolo Village, Pangkah Wetan Village, Gosari Village, Cangaan Village, Karangrejo Village, Tanjang Awan Village, Glatik Village, Ketapang Lor Village and Ngemboh Village. While Sekapuk Village became the only independent village in Ujungpangkah Subdistrict. While Kebonagung Village became the only village left behind in Ujungpangkah subdistrict. All villages that are research sites in Panceng Subdistrict are Prupuh Village, Sorowuti Village, Sumurber Village, Siwalan Village, Petung Village, Banyutengah Village, Patenan Village, Delegan Village, Ketanen Village and Campurejo Village in the category of Developing Village.